Pengaruh Store Atmosphere dan Kualitas Pelayanan Terhadap Minat Beli Konsumen Pada Damar Coffee Malang - NGUMAR NGUMAR; Agus Widarko; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTThis study aimed to know the Store Atmosphere impact, and service quality toward consumer purchase interest at Damar coffee Malang. The customer of Damar coffee are the population and sample of this research for about 75 respondents.This study collect the data by giving questionnaire and interview. In addition, the instrument of this study was SPSS Software 16 version. Then the method of analysis of this study uses slovin path analysis. The instrument test of this research was in the shape of validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, t test, F test. The result showed that partially store atmosphere and service quality have totally significant effect toward consumer purchase interest. Even, simultaneously it indicated that store atmosphere and the service quality also show significant effect toward consumer purchase interest. Keyword : Store Atmosphere, The Service quality and Consumer Purchase Interest